Implementation of the IDUKA-based Curriculum in forming outstanding students at SMK Muhammadiyah 7 Gondanglegi - Nabilla, Chintya Ainun (Maliki Interdisciplinary Journal, 2024)
The research aims to determine the implementation of the IDUKA curriculum in forming outstanding students at SMK Muhammadiyah 7 Gondanglegi. The method the author used for this research was the descriptive qualitative method. The curriculum management at SMK Muhammadiyah 7 Gondanglegi is structured in Dual System Education (PSG), with 60-70% of the application in practice and 30-40% in theory. The curriculum is synchronized with industry needs, including classrooms, practice rooms, tools, materials, and industry culture. IDUKA's role as a center for vocational schools is crucial in producing a generation that is qualified and able to compete in the world of work, following existing technological developments.